European Union : Publication of Financial Sector Assessment Program Documentation-Technical Note on Deposit Insurance. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
This article is an overview of existing deposit insurance in the European Union. There are various national deposit schemes that form the source of insurance. The schemes come up with various coverage, contributions, and fund sizes. The recent financial crisis has brought about a change in the coverage system. The main intention of this insurance is to enhance financial stability. The role of this insurance varies both within the EU and worldwide. This insurance is important to sustain financial integration and internal functioning.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet